2019
DOI: 10.1088/2057-1976/ab23e8
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in preload and the QRS amplitude in advanced heart failure patients

Abstract: To date, only invasive monitoring methods are available for continuous monitoring of the volume status of heart failure (HF) patients. The literature suggests that left ventricular (LV) volume status can in part be deduced from the electrocardiogram in healthy individuals in the experimental setting. The aim of this study was to evaluate if short-term changes in cardiac preload can be deduced from the QRS amplitude in advanced HF patients. We examined 19 non-decompensated advanced HF patients, listed for heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In heart failure patients, physiologic variation in QRS amplitude measured in the surface ECG were previously reported to be ±0.3 mV. 26 Based on the sensitivity of 0.07 mV/mL found in this study, the proposed technology can discern volume changes as small as 4 mL. The same study reported that The model was fitted with data from the small and large changes in volume as well as the hemorrhage intervention.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In heart failure patients, physiologic variation in QRS amplitude measured in the surface ECG were previously reported to be ±0.3 mV. 26 Based on the sensitivity of 0.07 mV/mL found in this study, the proposed technology can discern volume changes as small as 4 mL. The same study reported that The model was fitted with data from the small and large changes in volume as well as the hemorrhage intervention.…”
Section: Discussionmentioning
confidence: 61%
“…The same study reported that variability in QRS amplitude in the surface ECG remained unaffected by pacing. 26 As is evident, the LV volume sensor is likely to detect and report severe adverse events such as extreme LV emptying or overload conditions.…”
Section: Discussionmentioning
confidence: 99%